Direct and indirect effects of island size and wave exposure on shoreline arthropod diversity - Alma Strandmark; Elsa Aggemyr; Sara A. O. Cousins; Peter A. Hambäck (Journal of Biogeography, 2020)
Aim Available theories suggest that the species number increases with island size, but the relationship between island size and species density, the number of species per unit area, is less understood. Moreover, mechanisms connecting island size and species density are not always evident because small and large islands differ in physical characteristics other than island size. The purpose here was to disentangle direct and indirect effects of island size and wave exposure on the species density of arthropods from herb‐dominated shore habitats. Location Islands in the Stockholm Archipelago, Sweden. Taxon Spiders (Araneae) and beetles (Coleoptera). Methods We collected spiders and beetles on vegetated shores on islands of varying sizes, and used structural equation models to disentangle direct and indirect island size and wave exposure effects on species density. Results Island size affected diversity of web‐building spiders, predatory beetles and other beetles (detritivores and omnivores), direct and indirectly. Indirect effects arose because large islands have more trees and steeper slopes than small islands, both of which affected species occurrence. Because height above the sea level reduces the effect of wave exposure, there were effects of these variables on the forest cover and on the diversity of web‐building spiders. Finally, surrounding forest cover and diversity of flowering plants within sites increased diversity of herbivore beetles and cursorial spiders, likely because these sites provide more diverse resources. Main conclusions The result that predictors for species density vary between functional groups, with mechanisms that may or may not relate to island size, suggest potential developments in island biogeography theories. Future studies of island size effects should also attempt to quantify indirect effects, and not only total effects.

Seasonally varying marine influences on the coastal ecosystem detected through molecular gut analysis - Vasiliki Verschut; Alma Strandmark; Rodrigo Esparza‐Salas; Peter A. Hambäck (Molecular Ecology, 2019)
Terrestrial predators on marine shores benefit from the inflow of organisms and matter from the marine ecosystem, often causing very high predator densities and indirectly affecting the abundance of other prey species on shores. This indirect effect may be particularly strong if predators shift diets between seasons. We therefore quantified the seasonal variation in diet of two wolf spider species that dominate the shoreline predator community, using molecular gut content analyses with general primers to detect the full prey range. Across the season, spider diets changed, with predominantly terrestrial prey from May until July and predominantly marine prey (mainly chironomids) from August until October. This pattern coincided with a change in the spider age and size structure, and prey abundance data and resource selection analyses suggest that the higher consumption of chironomids during autumn is due to an ontogenetic diet shift rather than to variation in prey abundance. The analyses suggested that small dipterans with a weak flight capacity, such as Chironomidae, Sphaeroceridae, Scatopsidae and Ephydridae, were overrepresented in the gut of small juvenile spiders during autumn, whereas larger, more robust prey, such as Lepidoptera, Anthomyidae and Dolichopodidae, were overrepresented in the diet of adult spiders during spring. The effect of the inflow may be that the survival and growth of juvenile spiders is higher in areas with high chironomid abundances, leading to higher densities of adult spiders and higher predation rates on the terrestrial prey next spring.

Climate change effects on the Baltic Sea borderland between land and sea - Alma Strandmark; Arvid Bring; Sara A. O. Cousins; Georgia Destouni; Hans Kautsky; Gundula Kolb; Maricela de la Torre-Castro; Peter A. Hambäck (Ambio, 2015)

Has the invasive round goby caused new links in Baltic food webs? - Gustaf Almqvist; Alma K. Strandmark; Magnus Appelberg (Environmental Biology of Fishes, 2010)